t-5=-7+3t

Simple and best practice solution for t-5=-7+3t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t-5=-7+3t equation:


Simplifying
t + -5 = -7 + 3t

Reorder the terms:
-5 + t = -7 + 3t

Solving
-5 + t = -7 + 3t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-3t' to each side of the equation.
-5 + t + -3t = -7 + 3t + -3t

Combine like terms: t + -3t = -2t
-5 + -2t = -7 + 3t + -3t

Combine like terms: 3t + -3t = 0
-5 + -2t = -7 + 0
-5 + -2t = -7

Add '5' to each side of the equation.
-5 + 5 + -2t = -7 + 5

Combine like terms: -5 + 5 = 0
0 + -2t = -7 + 5
-2t = -7 + 5

Combine like terms: -7 + 5 = -2
-2t = -2

Divide each side by '-2'.
t = 1

Simplifying
t = 1

See similar equations:

| 20z-33=40 | | 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b |

Equations solver categories